The Role of Language Philosophy: Implications For Language Learning and Education - Widistari, Besse Sri; Nurhayati, St. (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
This article examines the principles of language philosophy and its ramifications for the field of education, particularly in language acquisition. Language philosophy is an academic discipline that examines the essence of language and its significance in human existence. Moreover, the philosophy of language is a multifaceted domain, making it challenging to ascertain the extent of its comprehension. Nonetheless, this does not imply that the subject of philosophical inquiry is ambiguous. Language philosophy, like other philosophical domains such as legais, natural, human, and social philosophy, examines, analyzes, and elucidates the essence of language as a substantive object of inquiry. Our study methodology employs a literature review and an analysis of topics in language philosophy. The research gathers data by analyzing many sources, such as books, scholarly journals, and additional materials. The study's findings indicate that language philosophy underscores the significance of contextual comprehension, the relativity of meaning, and the influence of language in constructing reality. These implications can enhance teacher and student awareness of the significance of language in the learning process.